Molecular Mechanism of Mesenchyme Homeobox 1 in Transforming Growth Factor β1–Induced P311 Gene Transcription in Fibrosis - Wei, Zhiyuan; Han, Chao; Li, Haisheng; He, Weifeng; Zhou, Junyi; Dong, Hui; Wu, Yuzhang; Tian, Yi; Luo, Gaoxing (Frontiers in Molecular Biosciences, 2020)
Organ fibrosis is characterized by excessive fibroblast, and extracellular matrix and the molecular basis are not fully elucidated. Recent studies have proven that P311, an 8-kDa conserved protein, could promote various organ fibrosis, such as skin, kidney, liver, and lung, partially through upregulating transforming growth factor β1 (TGF-β1) translation. However, the upstream regulators and mechanism of P311 gene regulation remain unclear, although we previously found that cytokines, hypoxia, and TGF-β1 could upregulate P311 transcription. Here, we aimed to elucidate the molecular mechanism of TGF-β1–induced P311 transcriptional regulation, focusing on mesenchyme homeobox 1 (Meox1). In this article, we identified the core promoter of P311 through bioinformatics analysis and luciferase reporter assays. Moreover, we demonstrated that Meox1, induced by TGF-β1, could bind to the promoter of P311 and promote its transcriptional activity. Furthermore, the effect of Meox1 on P311 transcriptional expression contributed to altered migration and proliferation in human dermal fibroblast cells. In conclusion, we identified Meox1 as a novel transcription factor of P311 gene, providing a new clue of the pathogenesis in fibrosis.